Model Lelang Jabatan Di Pemerintah Daerah Daerah Istimewa Yogyakarta - Yahya, MHD Rafi; Mutiarin, Dyah (Journal of Governance and Public Policy, 2015)
To get of state civil apparatus who performing good, so management human resources the government into importantconsideration. Governance of state civil apparatus good it is can be implemented by through a process positionpromotion structural good. The process position promotion structural good should be give birth to the leader orpublic official who competence and performing good.But later many phenomena the process position promotionstructural who gave birth to public official who incompetent and good performing. To comment on it and as bureaucracyreform the local government DIY implement position promotion structural model auction office. This study willsee how the implementation of the promotion model auction the employment in the local government Of DIY who inthis process use assessment center. The methodology writers included is the methodology qualitative. Data collectiontechniques used is interviews and documentation made it through observation non participants. Data analysis writerincluded is qualitative descriptive with draw conclusions and provide a or verify in the sentence so that eventuallydelivering on conclusion.To get structural officers competent and having a good performance local governmentsenvironment be conducted through a model auction promotion office. So in this research explain how promotionauction model office for second echelon within local government offices. Promotion as a model auction be implementedby local governments this analysis with three important element in promoting office. In this research alsopresents opinion of BKD about The act 5/2014 which regulates of state civil apparatus.